2007
DOI: 10.1002/pssa.200776313
|View full text |Cite
|
Sign up to set email alerts
|

The transfer doping of graphite and graphene

Abstract: It has been commonly thought that diamond is unique in its class in that it can undergo p‐type transfer doping when covered by a thin layer of electrolyte. In this study, density‐functional theory has been used to show that the work functions of graphite and graphene are low enough for transfer doping to occur between a graphite or graphene substrate and an aqueous adsorbate layer. The possible electrochemical reactions are the same as those favoured in the case of diamond, e.g. O2 + 2H2O + 4e– → 4OH– where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
67
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 32 publications
12
67
1
Order By: Relevance
“…49 Sque et al specifically suggested that graphene could undergo transfer doping to the aqueous oxygen redox couple. 50 Similar effects have been observed with multi-walled nanotubes. 51 Water films can occur on graphite, [52][53][54][55] diamond, 56,57 carbon nanotubes, 58 and graphene.…”
Section: Discussionsupporting
confidence: 65%
“…49 Sque et al specifically suggested that graphene could undergo transfer doping to the aqueous oxygen redox couple. 50 Similar effects have been observed with multi-walled nanotubes. 51 Water films can occur on graphite, [52][53][54][55] diamond, 56,57 carbon nanotubes, 58 and graphene.…”
Section: Discussionsupporting
confidence: 65%
“…The U G values reported in Table I (4.64-4.95 eV) are higher than theoretical values for ideal graphene, and higher also than values obtained from measurements performed in UHV. This can be ascribed to p-type doping from the lab environment, since both H 2 O and O 2 act as electron acceptors, 22,23 lowering E F and thus, increasing U G . Large changes ($200 meV) in the work function were observed from day to day due to chemical doping from adsorbents varying in the lab ambient.…”
Section: -mentioning
confidence: 99%
“…The notion of water behaving as electron acceptor when adsorbed on graphene is in accordance with recent theoretical studies. [27] An alternative mechanism that also appears plausible involves water adsorption on the residual oxygen containing groups that reduces the p-type doping. [28] However, our observations suggest that such a mechanism only plays a minor role, most likely due to the high concentration of water used here.…”
mentioning
confidence: 99%